(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
We concentrate on bi-shadowing property, it has important properties and applications in mathematics. In this paper some general properties of this concept are proved. Let be a metric space be maps have bi-shadowing property. We show the maps and have bi-shadowing property. Let be maps on a metric space have bi-shadowing property. We show the maps and have bi-shadowing property.